2014
DOI: 10.3945/ajcn.113.068122
|View full text |Cite
|
Sign up to set email alerts
|

BMI and all-cause mortality in older adults: a meta-analysis

Abstract: For older populations, being overweight was not found to be associated with an increased risk of mortality; however, there was an increased risk for those at the lower end of the recommended BMI range for adults. Because the risk of mortality increased in older people with a BMI <23.0, it would seem appropriate to monitor weight status in this group to address any modifiable causes of weight loss promptly with due consideration of individual comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
438
9
24

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 618 publications
(498 citation statements)
references
References 60 publications
27
438
9
24
Order By: Relevance
“…Our findings showed that men who were overweight and obese had lower mortality rates, consistent with research on the protective effect of high BMI with ageing (Janssen et al 2005) with the view that extra body weight, including lean tissue mass and fat mass, may provide protection against nutritional and energy deficiencies, metabolic stresses, the development of wasting and frailty and loss of muscle and bone density caused by chronic diseases (Janssen 2007). Our findings are in contrast to a recent meta-analysis that showed increased risk of mortality for older adults with a BMI above 33 kg/m 2 (Winter et al 2014). These differences could possibly due to the inclusion of both men and women in the meta-analysis, and due to inclusion of a younger population aged 65 and over, whereas our sample include men with mean age of 77 years.…”
Section: Discussioncontrasting
confidence: 62%
“…Our findings showed that men who were overweight and obese had lower mortality rates, consistent with research on the protective effect of high BMI with ageing (Janssen et al 2005) with the view that extra body weight, including lean tissue mass and fat mass, may provide protection against nutritional and energy deficiencies, metabolic stresses, the development of wasting and frailty and loss of muscle and bone density caused by chronic diseases (Janssen 2007). Our findings are in contrast to a recent meta-analysis that showed increased risk of mortality for older adults with a BMI above 33 kg/m 2 (Winter et al 2014). These differences could possibly due to the inclusion of both men and women in the meta-analysis, and due to inclusion of a younger population aged 65 and over, whereas our sample include men with mean age of 77 years.…”
Section: Discussioncontrasting
confidence: 62%
“…However, the average length of stay was one day shorter in the BMOS cohort, and the majority of the paper menu service cohort (59%) were admitted for orthopaedic surgery compared to 51% of the BMOS cohort admitted for general medical or gynaecological surgery (Table 1). Overall the study participants (paper menu and BMOS combined) had an average age of 65.1 years, with an average length of stay 9.1 days, an average body mass index (BMI) of 28.5 in the acceptable weight range adjusted for age ≥65 years (25-29.9) (16) , self-reported normal appetite and good health, and reflected a similar mix of "prescribed" diets and diagnoses. The longer length of stay of study participants compared to the hospital population was most likely a result of the study requirement for participants to be in hospital greater than 24 hours to be eligible (in order to comment on the meals and meal ordering process), and then a futher 48 hours to be able to complete all of the data collection.…”
Section: Resultsmentioning
confidence: 99%
“…A role for catabolic tissue loss in increased mortality risk during old age is suggested by epidemiological studies concluding that, in the elderly, moderately elevated BMI tends to be associated with improved survival (Janssen 2007;Auyeung et al 2010;Winter et al 2014). Yet analyses of the Adventist Health Study and Adventist Mortality Study, in which BMI was monitored serially, indicated that, among non-smoking men who maintain a relatively stable BMI during their mature years, mortality risk increases directly with BMIas one might expect from the health consequences of excess abdominal adiposity (Singh et al 1999;Singh et al 2011).…”
Section: Dietary Leucine Promotes Anabolism By Stimulating Mtorc1 Actmentioning
confidence: 99%